Biosensors in cardiology. T-CARE project: a preliminary study on an innovative wearable telemonitoring system. (19th May 2022) - Amati, F; Santobuono, VE; Bozza, N; Latorre, M; Memeo, R; Favale, S
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): REGIONE PUGLIA Introduction: The demographic trend evolution and the modification of health needs highlight the requirement for a novel organization of the healthcare system. Telemedicine allows the assistance of patients remotely, breaking down geographical barriers. Purpose: The aim of the present study was to assess the validity of a novel wearable system to monitor EKG, heart rate and pulse oximetry in patients with chronic cardiac diseases. The equippement included a T-shirt with electrodes and a band with a photopletimosgraphic sensor, connected to a tiny dock station (Figure 1, panel A). Methods: We enrolled 38 patients admitted to the coronary care unit at our hospital in Italy, 71% male, mean age 67 years, mean EF 45%. The main characteristics of the sample are listed in Table 1. The system was entirely automatic. Health parameters recording started as soon as patients wore T-shirt and band. Data were transmitted by Bluetooth technology to an external control unit. Recordings could be stored or could be checked in real time from a control room. Data were compared to measurements obtained by traditional monitoring system (telemetry). Results: The devices tested in this study showed a satisfying level of reliability in monitoring heart rate, pulse oximetry, QT interval, QRS complex duration, and onset of arrhythmic events. Indeed, the difference between traditional monitoring system and the new wearable equipment in acquiring health parameters was not statistically significant (Figure 1, panel B). However, alerts produced by arrhythmias different from atrial fibrillation were not completely reliable. Conclusions: The most important aspect of this new equipment was the need of minimal patient's interaction. This system was not inferior to traditional telemetry in recording health parameters.